2012
DOI: 10.1074/jbc.a111.257154
|View full text |Cite
|
Sign up to set email alerts
|

Cell entry of avian reovirus follows a caveolin-1-mediated and dynamin-2-dependent endocytic pathway that requires activation of p38 mitogen-activated protein kinase (MAPK) and Src signaling pathways as well as microtubules and small GTPase Rab5 protein.

Abstract: Authors are urged to introduce these corrections into any reprints they distribute. Secondary (abstract) services are urged to carry notice of these corrections as prominently as they carried the original abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…ARV has been reported to activate Ras, p38 MAPK, and src followed with caveolin-1 mediated endocytic pathway in dynamin-2 dependent [10]. ARV-induced phosphorylation of caveolin-1 (Tyr14) and dynamin-2 expression as well as Rac1 activation through activation of p38 MAPK and Src in the early stage of the virus life cycle is bene�cial for virus entry [10]. It was demonstrated that both p38 MAPK and Src are associated with cellular proteins caveolin-1 and dynamin-2.…”
Section: Caveolae/lipid Raft-dependent Endocytosismentioning
confidence: 99%
See 3 more Smart Citations
“…ARV has been reported to activate Ras, p38 MAPK, and src followed with caveolin-1 mediated endocytic pathway in dynamin-2 dependent [10]. ARV-induced phosphorylation of caveolin-1 (Tyr14) and dynamin-2 expression as well as Rac1 activation through activation of p38 MAPK and Src in the early stage of the virus life cycle is bene�cial for virus entry [10]. It was demonstrated that both p38 MAPK and Src are associated with cellular proteins caveolin-1 and dynamin-2.…”
Section: Caveolae/lipid Raft-dependent Endocytosismentioning
confidence: 99%
“…It was demonstrated that both p38 MAPK and Src are associated with cellular proteins caveolin-1 and dynamin-2. A novel role for p38 MAPK and Src signaling has been found to exert positive effects on caveolin 1 and dynamin 2 expressions, thereby enhancing ARV entry [10]. ARV traffics to early endosomes require the participation of microtubules and small GTPase Rab5 [10].…”
Section: Caveolae/lipid Raft-dependent Endocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…A number of viruses have been proved to enter host cells via the clathrin-dependent endocytosis pathway (12,33,36). Many other viruses have also been reported to enter host cells through the caveola-dependent pathway (3,17).…”
mentioning
confidence: 99%